Prevalence of depression and its potential contributing factors in patients with enterostomy: A meta-analytical review - Tang, Wymann Shao Wen; Chiang, Li Ling Christine; Kwang, Kay Wee; Zhang, Melvyn Wei Bin (Frontiers in Psychiatry, 2022)
Objective In patients with intestinal pathologies, the placement of a stoma bag affects multiple aspects of their perceived quality of life. This meta-analysis aims to evaluate the prevalence of depression among patients with enterostomy and to determine the underlying factors that could explain the potential heterogeneity of this prevalence. Methods Relevant published studies were identified by searching PubMed, Embase, PsycINFO, Cochrane, CINAHL, Scopus, and Web of Science until May 2022. The random-effects model was used to determine the pooled prevalence of depression among patients with enterostomy using cross-sectional studies from various countries. Meta-regression and subgroup analysis were performed to identify factors contributing to heterogeneity. Quality assessment of the included studies was conducted using the Newcastle-Ottawa scale for nonrandomized studies. Results The pooled prevalence of depressive symptoms among patients with enterostomy, as calculated using the random-effects model, was 41.6% (95% confidence interval [CI]: 25.4–59.7%, Q-value = 145.794, df = 8, p < 0.001, tau∧2 = 1.124, I∧2 = 94.513). The meta-regression found that mean age and gender were not significant moderators for the observed heterogeneity in prevalence. Subgroup analysis according to the indications for enterostomy formation showed that the prevalence of depression was highest in patients with colorectal cancer, at 34.4% (95% CI: 27.2–42.4%). Subgroup analysis by region showed that patients in Africa had the highest prevalence of depression, at 88.2% (95% CI: 76.1–94.6%), compared to other regions. Subgroup analysis by stoma indication was not significant. Conclusion This meta-analysis reports that the pooled prevalence of depression among patients with enterostomy is 41.6%. Indications for enterostomy formation, as well as geographical region, were identified as potential sources of heterogeneity. These findings highlight the need for appropriate psychosocial support and interventions at different stages of enterostomy placement.